Road network supply efficiency in Cape Town, South Africa and its link to the incidence of road traffic crashes: an evaluation of equity - Ter Huurne, Dominique Andrea (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.